New Data Systems and Products at the Permanent Service for Mean Sea Level - Holgate, Simon J.; Matthews, Andrew; Woodworth, Philip L.; Rickards, Lesley J.; Tamisiea, Mark E.; Bradshaw, Elizabeth; Foden, Peter R.; Gordon, Kathleen M.; Jevrejeva, Svetlana; Pugh, Jeff (Journal of coastal research, 2013)
Holgate, S.J.; Matthews, A.; Woodworth, P.L.; Rickards, L.J.; Tamisiea, M.E.; Bradshaw, E.; Foden, P.R.; Gordon, K.M.; Jevrejeva, S., and Pugh, J., 2013. New data systems and products at the Permanent Service for Mean Sea Level. Sea-level rise remains one of the most pressing societal concerns relating to climate change. A significant proportion of the global population, including many of the world's large cities, are located close to the coast in potentially vulnerable regions such as river deltas. The Permanent Service for Mean Sea Level (PSMSL) continues to evolve and provide global coastal sea-level information and products that help to develop our understanding of sea-level and land motion processes. Its work aids a range of scientific research, not only in long-term change, but also in the measurement and understanding of higher frequency variability such as storm surges and tsunamis. The PSMSL has changed considerably over the past 10 years, and the aim of this paper is to update the community about these changes as well as provide an overview of our continuing work.